Next-generation sequencing and immuno-informatics for designing a multi-epitope vaccine against HSV-1-induced uveitis - Cao, He; Cao, Zhi; Han, Yue; Shan, Jing (Frontiers in Immunology, 2025)
BackgroundUveitis, characterized by intraocular inflammation, poses significant clinical challenges, often leading to vision impairment or blindness. Herpes Simplex Virus type 1 (HSV-1) is a major cause of virus-induced uveitis. This study aims to design a novel multi-epitope vaccine targeting HSV-1 glycoproteins B, C, D, H, and L using an immuno-informatics approach, which are essential for viral entry and pathogenesis.MethodsThe study identified epitopes for CD8+ T cells, CD4+ T cells, and B cells within the target glycoproteins. These epitopes were systematically evaluated for conservancy, immunogenicity, non-allergenicity, non-glycosylated regions, and binding affinities. A multi-epitope construct was designed, incorporating these epitopes along with an adjuvant, a PADRE sequence, and suitable linkers. In-silico immune simulations were performed to evaluate the vaccine’s potential to activate both innate and adaptive immune responses. Molecular docking simulations assessed the binding interactions between the multi-epitope vaccine and Toll-like receptor (TLR-9).ResultsThe selected epitopes demonstrated high conservancy, immunogenicity, and non-allergenicity. The multi-epitope construct effectively activated cytokine production, immunoglobulin secretion, and T cell responses in in-silico immune simulations. Molecular docking simulations showed strong binding interactions between the vaccine and TLR-9, suggesting enhanced antigen presentation capabilities.ConclusionThis comprehensive immuno-informatics approach provides a precision immunotherapy strategy for uveitis by leveraging computational modeling and predictive analytics to design a multi-epitope vaccine for HSV-1. The in-silico results indicate the vaccine’s potential efficacy in activating immune responses. Future experimental validation and clinical studies are necessary to confirm the safety and efficacy of this proposed vaccine in managing uveitis and preserving vision.